Camel's neglected potential - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
By the year 2000 the potential deficit of meat production in sub-Saharan Africa is expected to be between 3 and 8 million tonnes. This prediction has been made by international organizations such as the FAO, the World Bank and the UN Economic...